China’s initial allocation of interprovincial carbon emission rights considering historical carbon transfers: Program design and efficiency evaluation - Huijun Zhou (Elsevier, 2021)
Establishing a fair and reasonable initial allocation scheme for carbon emission rights is a prerequisite for the efficient and stable operation of the carbon market and an important guarantee for China to achieve its emission reduction target. This study considers the historical transfer of carbon emissions and measures the cumulative net carbon emissions of China's provinces based on the principle of consumer responsibility. It draws up an initial allocation plan for carbon emission rights in China's provinces in 2020, based on the principles of equity, efficiency, and sustainability. The carbon emission and carbon intensity efficiencies of the provinces under this distribution scheme were also evaluated. The results show that the historical net carbon export area mainly consists of energy-intensive provinces and economically underdeveloped poor and remote provinces. Additionally, the historical net carbon import area mainly consists of energy-starved and economically developed provinces. Provinces with high-value ecological services (Xinjiang, Heilongjiang, and Inner Mongolia) or with large economies and dense populations (Shandong, Guangdong, and Sichuan) will receive higher carbon emission rights, while those with developed economies (Shanghai, Beijing, and Tianjin) will receive lower carbon emission rights. Provinces with a good ecological environment (Inner Mongolia, Heilongjiang, and Xinjiang) as well as certain economically underdeveloped western provinces (Chongqing, Sichuan, and Yunnan) will have abundant carbon space in the future. Provinces with rapid economic development (Beijing, Shanghai, and Jiangsu) and resource-based provinces (Shanxi and Liaoning) with a high historical carbon output have little carbon space. Considering the historical carbon transfer, the carbon emission rights allocation system will benefit resource-based industrial provinces (Shanxi, Inner Mongolia, and Liaoning) and less developed western provinces (Shaanxi, Ningxia, and Xinjiang) in improving their carbon emission efficiency. This study provides a new research idea for formulating a more equitable and efficient allocation scheme for carbon emission rights.